Picket and demonstration in Malaysia - Ismail, Fadillah; Humaid Alhosani, Adnan Ali Hassan; Chan, Shiau Wei; Nojumuddin, Nur Syereena (Penerbit Uthm, 2019)
Picket refers to a person or a group of people who assemble in front the entrance of the employer’s premises or other venue. It is an industrial action done by unionized workers as a protest. They are trying to persuade others such as co-workers, workers of other firms and customers from not entering the particular premise during a strike. Also, they are trying to persuade the customers from not conducting business with the premises. In a lawful way, picketing usually required the approval from union ballot (Business Dictionary, 2018).